161k views
3 votes
2) Solve the system of equations using substitution.
2x – 9y = 14
x= -6y +7

User Hsu
by
5.7k points

2 Answers

3 votes

Answer:

(7,0) ---> (x = 7) and (y = 0)

Explanation:

2x – 9y = 14

x= -6y +7 <-- (Substitute for x to above equation)

---------------------------------------------------------------------------------------------------------

2(-6y +7)– 9y = 14

-12y + 14 - 9y = 14 <-- combine like terms

-21y + 14 = 14

-14 = -14 <-- inverse operation on both sides

-21y = 0 <-- Divide

y = 0 <--- Substitute for y to get x ↓

-------------------------------------------------------------------------------------------------------

2x – 9y = 14

2x – 9(0) = 14 <-- Substituted y from above

2x = 14 <-- Divide

x = 7

User Aaron Barker
by
5.4k points
0 votes
2(-6y)-9y = 14
-12y - 9y = 14
-21y = 14
y = -2/3
User Wsl
by
5.8k points